Facial nerve outcome score: a new score to predict long-term facial nerve function after vestibular schwannoma surgery - Di Perna, Giuseppe; De Marco, Raffaele; Baldassarre, Bianca Maria; Lo Bue, Enrico; Cofano, Fabio; Zeppa, Pietro; Ceroni, Luca; Penner, Federica; Melcarne, Antonio; Garbossa, Diego; Lanotte, Michele Maria; Zenga, Francesco (Frontiers in Oncology, 2023)
Patients’ quality of life (QoL), facial nerve (FN) and cochlear nerve (CN) (if conserved) functions should be pursued as final outcomes of vestibular schwannoma surgery. In regard to FN function, different morphologic and neurophysiological factors have been related to postoperative outcomes. The aim of the current retrospective study was to investigate the impact of these factors on the short-term and long-term FN function after VS resection. The combination of preoperative and intraoperative factors resulted in designing and validating a multiparametric score to predict short- and long-term FN function. A single-center retrospective analysis was performed for patients harboring non-syndromic VS who underwent surgical resection in the period 2015-2020. A minimum follow-up period of 12 months was considered among the inclusion criteria. Morphological tumor’s characteristics, intraoperative neurophysiological parameters and postoperative clinical factors, namely House-Brackmann scale (HB), were retrieved in the study. A statistical analysis was conducted in order to investigate any relationships with FN outcome and to assess the reliability of the score. 72 patients with solitary primary VS were treated in the period of the study. A 59.8 % of patients showed an HB < 3 in the immediate postoperative period (T1), reaching to 76.4% at the last follow-up evaluation. A multiparametric score – Facial Nerve Outcome Scores (FNOS) – was built. The totality of patients with FNOS grade A showed an HB value < 3 at 12 months, decreasing to 70% for those with FNOS grade B, while 100% of patients with FNOS grade C showed an HB value ≥ 3. The ordinal logistic regression showed three times increasing probability to see an HB value ≥ 3 at 3-month FU for each worsening point in FNOS score (Exp(B) 2,999 p < 0.001) that was even more probable (Exp(B) 5.486 p < 0.001) at 12 months. The FNOS score resulted to be a reliable score, showing high associations with FN function both at short- and long-term follow-up. Although multicenter studies would be able to increase its reproducibility, it could be used to predict the FN damage after surgery and the potential of restoring its function on the long-term period.